PENGARUH PENERAPAN SISTEM E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA PEKANBARU TAMPAN - Aprillia, Annisha; Gusnardi, Gusnardi; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to analyze the influence of E-Filling System Implementation on Compulsory Compliance on KPP Pratama Pekanbaru Tampan. The population of this research is Individual Taxpayer registered as Taxpayer in KPP Pratama Pekanbaru Tampan. The samples used in this study were 100 respondents. The questionnaire has been tested for its validity before the study. The classical assumption test used is the normality test. Hypothesis test used is simple linear regression. The results of this study indicate that there is a positive and significant influence implementation of E-Filling System to Taxpayer Compliance in Pratama Pekanbaru Tampan. This is proven through simple linear regression analysis obtained Adjusted R Square value of 0.325, which can be interpreted that the influence of E-Filling System Application to Taxpayer Compliance is 32.5%. The result of the statistical t test yields a significance value smaller than significant 0.000 <0,05. The value of regression coefficient X 0,379 with the number of kostanta 32,436. The equation of the regression line is Y = 32.436 + 0.379X. This means the higher the Implementation of E-Filling System, the higher the Taxpayer Compliance will be.Keywords: E-Filling, Taxpayer Compliance.